Eksplorasi Etnomatika dalam Tatanan Bangun Ruang dan Bangun Datar Pada Kawasan Alun-Alun Kota Surabaya - Yuliati, Dian; Salsabila; Achmad Fachril Yusuf Ababil; Sharenada Norisdita Wahyudi; Moh. Aditya Sirojul Hilmi; Panreshma Rizkha Ambadar (Universitas Airlangga, 2024)
Mathematics is a science that has been studied from elementary to high school and continues to be developed up to university. Mathematical concepts can be linked to social and cultural concepts called ethnomathematics. Ethnomathematics in community life can be implemented in the form of buildings. This research aims to explore geometric shapes and explain mathematical concepts in the Surabaya City Square building as an effort to help understand geometric concepts in flat shapes and spatial shapes. The method used in this research is a qualitative method with an ethnographic approach and literature study. The research results show that Surabaya City Square is a historic building that implements geometric concepts in terms of buildings. Mathematical concepts in the shape of the Surabaya City Square building include the concept of flat shapes consisting of rectangles, triangles, trapezoids, circles and ellipses, as well as the concept of spatial shapes consisting of triangular prisms, blocks, tubes and balls. It is hoped that this research can provide understanding and make learning interesting, especially in mathematics.